Metabarcoding–approach–based profiling reveals dynamic nature of sustainable tillage practices on nematode communities in corn–soybean cropping systems - Jerry Akanwari; Md Rashedul Islam; Ping Liang; Tahera Sultana (Scientific Reports)
Abstract Despite extensive research on tillage and its impact on nematode communities, little is known about the impact of occasional tillage within no–tillage practices. Occasionally tilling the soil can minimize the negative effects of conventional tillage and no–tillage practices especially in clayey soils. A tillage system that maximizes all the economic and environmental benefits but increases herbivore nematodes while reducing beneficial free–living nematodes may pose long–term agronomic challenges. In this study, we investigated the impact of conventional tillage (CT), minimum tillage (MT), and occasional tillage within no–tillage (NT) systems, on nematode communities in corn–soybean cropping systems in Ontario, Canada using metabarcoding approach. Soil samples were collected at 0–5 cm and 5–20 cm depths during planting and before harvesting of corn/soybeans in 2021 and 2022. The results showed that tillage significantly influenced nematode community structure and distribution within the soil profile. Beneficial free–living nematodes were abundant at 0–5 cm (> 70%), while herbivores dominated at 5–20 cm. The MT and NT systems supported a higher relative abundance of bacterivores, particularly Rhabditis, at both depths. Bacterivore populations were 1.7 times higher in MT than in CT at the corn/soybean maturity stage. The CT system favoured herbivore nematodes, especially Pratylenchus, with 47% higher populations at 0–5 cm and 76% higher at 5–20 cm compared to MT and NT. The CT was initially characterized by high maturity index and structure index values, possibly due to legacy effects; however, both metrics declined over time, whereas values under NT increased. The plant–parasitic index was elevated in both CT and NT but differed in the dominant functional guilds. The nematode channel ratio was higher under CT and MT, signaling a stronger bacterial pathway, while NT gradually shifted toward a more fungal microbial channel. The soil organic matter (OM), total carbon and total organic carbon were significantly higher at the 0–5 cm depth in the MT and NT systems. Correlation analysis identified pH, OM, total nitrogen and cation exchange capacity as the key soil properties shaping the structure of nematode communities. Our findings suggest that MT and NT can enhance soil health and long–term resilience against herbivores in corn–soybean cropping systems.